Inferior clinical outcomes after femur fracture in the obese are potentially preventable. Issue 11 (November 2019) - Bryant, Mary K.; Parrish, Matthew; Roy, Sara; Udekwu, Pascal; Farrell, Megan; Schinco, Miren; Ganga, Sarat
Highlights: After femur fracture, higher BMI puts patients at risk for longer HLOS and increased rates of systemic complications. Mediation models indicate adverse outcomes associated with obesity are caused by delayed mobility, a non-patient factor. Clinical strategies should be directed at early mobilization after femur fracture to minimize morbidity. Abstract: Introduction: Obese patients with operative orthopedic trauma have increased risk of adverse outcomes, although the mechanisms accounting for the relationship remain unknown. This study examines the effect of body mass index (BMI) on outcomes after femur fracture fixation, and explores the mediating effects of pathophysiologic factors and clinical management. Methods: A retrospective chart review was performed of adult patients with femur fractures undergoing surgical fixation at a Level 1 trauma center from 2010 to 2016. Demographics, Injury Severity Score (ISS), Glasgow Coma Scale (GCS) and mechanism of injury (MOI) were collected along with operative data and complications. Primary outcomes were hospital length of stay (HLOS), ICU length of stay (ICU-LOS), mortality, complications, and time to mobility (time first out of bed, TFOB). Bivariate correlations and multiple regression models were used to examine the relationship between BMI and outcomes. Path analysis tested whether the relationship between BMI and clinical outcomes was mediated by differences in 1) clinical management, or 2) physiologic variables. Results: Of 333 patients included, the majority were male (57.4%) with a mean age of 43.4 (22.7) years and ISS of 12.5 (6.8). Predominant MOIs were motor vehicle crashes (42.8%) and falls (34.5%). There was no association between BMI category and age, ISS, or GCS. In univariate analysis, higher BMI was linked to longer HLOS ( r = .12), longer ICU-LOS ( r = .15), longer TFOB, ( r = .18), and higher number of complications ( r = .12), p < 0.05. Controlling for age and ISS, obese patients had 6.66 times the odds of respiratory failure (p = 0.021, 95% CI 1.3, 33.3) and a 3.88 odds of any complication (p = 0.020, 95% CI 1.24, 12.1) compared to their normal weight counterparts. For every one point increase in BMI, time first out of bed was delayed 2.3 h (p < 0.001; 95% CI 1.08, 3.62). The effect BMI on poor outcomes was accounted for by delayed mobility (longer TFOB) in a mediation model. Conclusions: Higher BMI increases the risk of longer hospital stays and systemic complications. Mediation models indicate that the adverse clinical outcomes associated with obesity are explained by delays in mobility, an intervenable factor. Clinical strategies should be directed at early mobilization to minimize morbidity.